Deep learning can reduce acquisition time of T2-weighted image in brain imaging - Eman Hassan El-Saeed Abou-ELMagd; Sabry Alameldin Elmogy; Dina Gamal Abdelzaher (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background We used the deep learning-based reconstruction algorithm to reduce the scan time for brain T2-weighted images (T2WI) with reduction of image noise and preservation of image quality. The current prospective study included 22 cases; they were subjected to brain magnetic resonance. The aim was to investigate how much could deep learning reduce acquisition time of T2WI in brain imaging. Results There was a statistically significantly higher air noise (N) in conventional image analysis versus DL image analysis, but no statistically significant difference in image signal (S). Signal-to-noise ratio (SNR) was statistically significantly higher in DL image analysis versus conventional image analysis. This showed that the improvement in SNR was explained by significant decrease in N without significant change in S. Conclusions We concluded that deep learning-based reconstruction provides advantages of maintaining optimum image quality, reduction of image noise and obtaining the images in short time while applied during acquisition of brain magnetic resonance imaging (MRI) by T2WI. Yet, the diagnostic value of this technique to be verified, large-scale clinical studies should be conducted on this issue.